Effect of public relations activities conducted in professional football clubs on fan satisfaction - Hakan Salim Caglayan; Celalettin Bayar (Türk Spor ve Egzersiz Dergisi)
This study was conducted in an attempt to examine effect of public relations activities conducted in professional football clubs on fan satisfaction. In this study, survey model was employed to uncover current situation. The research sample was composed of a total of 699 fans (nmale=535 and nfemale=164) including 200 Fenerbahçe fans (nmale=179 and nfemale=21), 100 Beşiktaş Fans (nmale=2 and nfemale=98), 201 Galatasaray Fans (nmale=178 and nfemale=23) and 198 Gençlerbirliği Fans (nmale=176 and nfemale=22), who were selected with random sampling method from football teams played in Super Toto Super League at Turkey Football Federation 2011-2012 Football Season. “Fan Satisfaction Scale of Public Relations Activities” consisting of a total of 25 items and 5 sub-dimensions (recognition-identification, social responsibility, service activity, corporate governance and sportive activity) was developed in an effort to serve the purpose of the study. Research data were collected using developed relevant scale and “Personnel Information Form”. In analyzing the data, necessary statistical analyses were carried out in accordance with the rules needed to be followed in the development process. Mann-Whitney U Test and Kruskal-Wallis One-Way Analysis of Variance have been used, respectively, for pairwise comparisons and multiple comparisons since all sub-dimensions were not shown normal distribution after test of normality performing for sub-dimensions of the scale that had provided its validity and reliability. Mann-Whitney U Test was employed to determine this difference arising from which groups in the cases where statistically significant difference was found in consequence of Kruskal–Wallis one-way analysis of variance in multiple comparisons. α=0.05 was chosen for level of significance in the study. As a result of the study, it was determined that, on the one hand, team fans were “satisfied with” the dimensions “recognition-identification, service activity, corporate governance and sports activity" of Public Relations Activities performed by football clubs which they support, on the other hand, they were “neither satisfied nor dissatisfied with” the dimension “social responsibility”, namely, levels of their satisfaction were lower than those of other dimensions. It was determined that, on the one hand, the fans participated in the research differed significantly in the sub-dimension “sportive activity" of Fan Satisfaction Scale of Public Relations Activities according to the variable “gender”, on the other hand, they did not differ significantly in other sub-dimensions according to the variable “gender”. It was determined that the fans taken part in the research differed significantly in all the sub-dimensions of Fan Satisfaction Scale of Public Relations Activities according to the variables “age, educational level and marital status”. It was determined that, on the one hand, the fans involved in the research differed significantly in the sub-dimensions “social responsibility, service activity and corporate governance” of Fan Satisfaction Scale of Public Relations Activities according to the variable “level of income”, on the other hand, they did not differ significantly in other sub-dimensions according to the variable “level of income”.